Developing Sub‐Nanofibers in Electrospun Nylon‐6 Web by Controlling the Parameters of the Process. Issue 1 (January 2014) - Rahmani, H.; Karimi, M.; Bulavin, Leonid; Guenet, Jean‐Michel
Summary The aim of the present work is to subject the polyelectrolyte solutions of nylon‐6 in formic acid undergoes an electrospinning process. To form sub‐nanofibers (<50 nm in diameter) within the electrospun nanofibers mats, polymer concentration, applied voltage, solution temperature and environmental condition were chosen as variables. Scanning electron microscope was used to probe the presence of sub‐nanofibers into the electrospun mat. To appear sub‐nanofibers significantly, during the process of electrospinning, an optimum condition was obtained by finding a proper concentration of solution, applied voltage and temperature of solution which were 15 wt.%, 22 kV and 25 °C, respectively.